MANAJEMEN FISIOTERAPI PREVENTIVE AND PROMOTIVE POLINEUROPATI PADA LANSIA DI DESA SIGODANG KAB. SIMALUNGUN - Isa Harpika Br. Ginting; Yeni Trisna Purba; Bunga Shinta Pratiwi Tarigan (Yayasan Nusantara Hasana Berdikari, 2022)
The study indicates that physiotherapy interventions have a positive effect on improving muscle strength, balance, and cognitive function, while also reducing the risk of falls. The program was implemented through a combination of physiotherapy exercises, health education, and brain gym activities to enhance awareness and cognitive-related abilities. An unsupportive environment and limited access to medical services present major challenges, requiring an individualized approach to care. After 12 weeks of intervention, participants showed significant improvement in physical strength and balance. The recommendations include modifying the home environment and providing family and healthcare support to ensure safety and ongoing care.